Sekuritisasi Pengungsi: Melihat Bagaimana Narasi Media Sosial dalam Membentuk Persepsi Keamanan Nasional - Andi Milhan (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2026)
The escalation of negative sentiment in the digital space towards Rohingya refugees in Indonesia throughout 2023-2026 has reflected a shift in public perspectives, from humanitarian principles to restictive rejection. This study aims to analyze how digital discourse on TikTok dan Instagram platforms frames the Rohingyan refugee issue as a national security threat through the lens of Barry Buzan`s Securitization Theory and Ruth Wodak`s Critical Discourse Analysis (AWK). This study uses qualitative methods with note-taking techniques and filtering hastag-based viral data related to refugee rejection. The results show that the securitization process was successfully driven by three main typologies of netizen narratives: domestic socio-economic jealousy, delegetimization of Internasional authorities (UNHCR) by referring to popular legal discourse on the 1945 Constitution, and demands for an active role for the military (TNI AL) and Polair at maritime borders. The accumulation of speech acts that have gone viral on social media is evidence of the creation of strong horizontal pressure, thus urging the Indonesian goverment to review its policies towards a more restrictive direction (viral-based policy) to prioritize national soverignity and security over global humanitarian commitments.